Analisis Fundamental Makro, Fundamental Mikro, Terhadap Nilai Perusahaan Dengan Struktur Kepemilikan, Kinerja Keuangan Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar Di BEI - Salva Dewi Ambarwati; Hwihanus Hwihanus (Akuntansi, 2024)
financial performance as an intervening variable, this study has is to determine how firm value is influenced by macro and micro fundamentals, ownership structure, and financial performance in companies listed on the Indonesia Stock Exchange (IDX), this analysis technique uses Smart PLS version 4. Of the 9 hypotheses made, 4 hypotheses were accepted and 5 hypotheses were rejected. Financial performance and ownership structure have been shown to act as mediators between firm value, macro fundamentals, and micro fundamentals. Based on the findings, investors should consider ownership structure, micro fundamentals, macro fundamentals, and financial performance when making investment decisions. To increase its value, a business should also pay attention to its financial performance. Based on the findings of this study, in making investment decisions, investors should consider ownership structure, micro fundamentals, macro fundamentals, and financial performance. In addition, organizations need to focus on their financial performance to increase firm value.